ANALYSIS OF FACTORS AFFECTING THE QUALITY OF FINANCIAL STATEMENTS REGENCY APPARATUS WORK UNIT IN THE GOVERNMENT OF ACEH TAMIANG REGENCY WITH ORGANIZATIONAL COMMITMENTS AS MODERATING VARIABLES - Adrian, Rica (Asosiasi Dosen Akuntansi Indonesia, 2019)
The purpose of this study is to analyse the effect of government internal control systems (GICS), human resource competencies (HR), utilization of information technology (IT), application of Government Accounting Standards (GAS) and the role of internal audit with organizational commitment as a moderating variable on the quality of financial statements Regency Government Work Unit in Aceh Tamiang Regency Government. This type of research is causal research. The population in this study was 88 people, consisting of the Head of the Regency Government Work Unit (Budget User) and the Financial Administration Officer in the entire Regency Government Work Unit (SKPK) of the Aceh Tamiang District Government, totaling 44 Regency Government Work Unit. The method of determining the sample with the census method, so that the entire population is used as a research sample. The data in this study are primary data and data collection techniques using a questionnaire. Hypothesis testing uses the Structural Equation Model (SEM) with the help of the Square Least Square (PLS) program. The results of this study prove that GICS, human resource competence, IT technology utilization, GAS application and the role of internal audit have a significant effect on the quality of financial statements simultaneously. Partially, the GICS system, IT utilization and the role of internal audit have a positive and significant effect on the quality of financial statements, while HR competence and GAS application have a positive but not significant effect on the quality of financial statements. Organizational commitment as a moderating variable can moderate the effect of GICS on Regency Government Work Unit financial statements but organizational commitment has not been able to moderate the relationship between HR competencies, IT utilization, GAS implementation and the role of internal audit on the quality of Regency Government Work Unit?s financial statements in the Government of Aceh Tamiang Regency.